2014
DOI: 10.1590/1519-6984.12612
|View full text |Cite
|
Sign up to set email alerts
|

Helicometrina nimia Linton, 1910 (Digenea: Opecoelidae) in dusky grouper Epinephelus marginatus (Lowe, 1834) (Teleostei: Serranidae) from southeastern Brazil

Abstract: Helicometrina nimia (Opecoelidae) is a digenean with wide distribution. Fish families most commonly used as hosts for H. nimia are Serranidae, Pomodasydae, Scorpaenidae and Clinidae. In the present study, a new host and a new host locality are presented for the species. A description of the studied specimens, besides comments concerning its taxonomic status and biometrically compared tables of H. nimia reports are given. The taxonomic status of members of Helicometrina has been questionable. The greatest contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
1
Order By: Relevance
“…The intensity of the parasite species was 10.1, 5.4, and 8.6 in Labrisomus philippii, Paralabrax humeralis, Acanthistius pictus respectively. Roumbedakis et al [41] reported that H. nimia infection rate was 19.49%,the mean abundance was 1.19 ± 4.02, and the mean intensity was 6.13 ± 7.33.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the parasite species was 10.1, 5.4, and 8.6 in Labrisomus philippii, Paralabrax humeralis, Acanthistius pictus respectively. Roumbedakis et al [41] reported that H. nimia infection rate was 19.49%,the mean abundance was 1.19 ± 4.02, and the mean intensity was 6.13 ± 7.33.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of different parasites has been reported in dusky grouper populations [ 6 , 7 , 8 , 9 , 10 , 11 ]. In particular, natural outbreaks associated with gnathiid isopod larvae have been observed in wild and captive E. marginatus , in some cases associated to significant haematophagia [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Otra especie con los mayores índices parasitológicos fue el trematodo H. nimia, el cual tiene una amplia distribución geográfica y de hospederos (Roumbedakis et al, 2014). Las familias de peces que usualmente usa como hospedero son las familias Serranidae, Pomodasydae, Scorpaenidae y Clinidae (Inzunza et al, 1989).…”
Section: Discussionunclassified